Randomised controlled trial comparing European standard class 1 to class 2 compression stockings for ulcer recurrence and patient compliance. Issue 4 (19th October 2012) - Clarke‐Moloney, Mary; Keane, Niamh; O'Connor, Veronica; Ryan, Mary Anna; Meagher, Helen; Grace, Pierce A; Kavanagh, Eamon; Walsh, Stewart R; Burke, Paul E
<x xml:space="preserve">Abstract</x> The aim of this study was to determine the rate of venous ulcer recurrence and the level of compliance in patients wearing European class 1 or class 2 compression stockings. A total of 100 patients with healed venous leg ulcers were recruited, and were randomised to either class 1 (n = 50) or class 2 (n = 50) compression stockings. Follow‐up was at 1 week, 3, 6, 9 and 12 months to monitor ulcer recurrence and compliance. Patients had a duplex scan to identify the source of venous incompetence. The rate of ulcer recurrence after 12 months was 16·1%, and the difference in recurrence rate between classes was not statistically significant (P = 0·287) although greater numbers in class 1 developed a recurrence. Participants (88·9%) were compliant; non‐compliant patients were at a significantly greater risk of recurrence (P≤ 0·0001). Thirteen patients had both superficial and deep incompetence; those randomised to class 1 stockings (n = 4) developed ulcer recurrence. Patients with a history of multiple episodes of ulceration were more likely to develop a recurrence (P = 0·001). The lowest venous ulcer recurrence rates were seen in patients who were compliant with hosiery regardless of the compression level. Patients with both superficial and deep incompetence had a lower rate of recurrence with class 2 compression.